2016
DOI: 10.5152/eajem.2016.52386
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Head Trauma in Turkey and Impact of Multidisciplinary Team Establishment Efforts on Case Finding and Management: Preliminary Findings

Abstract: Aim: Abusive head trauma (AHT) is the most common cause of death as the result of child abuse. A task force is planned to provide training on AHT to professionals in different disciplines on clinical presentation, diagnostic workup, and organization of multidisciplinary evaluation at the hospital and community levels. This study reports on the preliminary findings of the pre-intervention phase of a larger study. Materials and Methods:This is a descriptive, retrospective study exploring the rates of documentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In Estonia, Talvic et al found that all of the 26 AHT cases that were discovered and diagnosed between 1997 and 2003 were <1 year [ 16 ]. A study conducted in Turkey stated that 88% of all AHT cases were under the age of two years and males represented 56% of the cases [ 20 ]. According to Frasier [ 21 ], the increased vulnerability may be related to infants’ close contact with their caregivers and need constant care as compared with older children.…”
Section: Discussionmentioning
confidence: 99%
“…In Estonia, Talvic et al found that all of the 26 AHT cases that were discovered and diagnosed between 1997 and 2003 were <1 year [ 16 ]. A study conducted in Turkey stated that 88% of all AHT cases were under the age of two years and males represented 56% of the cases [ 20 ]. According to Frasier [ 21 ], the increased vulnerability may be related to infants’ close contact with their caregivers and need constant care as compared with older children.…”
Section: Discussionmentioning
confidence: 99%